2021
DOI: 10.3390/agronomy11061190
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Responses of Two Contrasting Lentil Genotypes to PEG-Induced Drought Stress

Abstract: Among abiotic stresses, drought is undoubtedly one of the most severe environmental factors for a wide range of major crops, leading to considerable yield and economic losses. The adverse effects in crop yield reflect the result of a series of morphological and physiological changes but also changes in signaling pathways, transcriptional and post-transcriptional regulation of stress-responsive genes, and metabolic adaptations. Despite the exhausting studies elucidating plants’ metabolic response to drought, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 108 publications
(130 reference statements)
0
5
0
Order By: Relevance
“…In lentil ( Lens culinaris Medik. ), significant changes in xylose accumulation were observed during osmotic drought stress [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…In lentil ( Lens culinaris Medik. ), significant changes in xylose accumulation were observed during osmotic drought stress [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…L-asparagine responded to stress in tolerant Elpida stronger than in susceptible Flip03-24L (20 fold vs. 7 fold). Carboxylic acid raised in stress with a stronger effect in the tolerant Elpida: seven-ten-fold in Elpida vs. five-six-fold in Flip03-24L for 2-ketoglutaric acid, five-fold vs. no change for malonic acid and four-fold vs. two-three-fold for citric acid [104].…”
Section: Metabolomics For Abiotic Stress Responses and Tolerancementioning
confidence: 99%
“…Arachis hypogea D-pinitol, D-chiro-inositol, myo-inositol [41] Ceratonia silique D-pinitol, allo-inositol, D-chiro-inositol, bornesitol, scyllo-inositol, myo-inositol [41,43] Cicer arietinum D-pinitol, D-chiro-inositol, myo-inositol, galactosyl-inositol, galactosyl-pinitol, ciceritol [43,44] Erythrina edulis D-chiro-inositol, myo-inositol [44] Fagopyrum esculentum D-chiro-inositol, myo-inositol, galactosyl-inositol, fagopyritol [43] Glycine max D-pinitol, D-chiro-inositol, myo-inositol, fagopyritol, galactosyl-pinitol [43,44,54] Glycyrrhiza glabra D-pinitol [52] Latirus sativus bornesitol, myo-inositol, galactosyl-inositol [43] Lens culinaris D-pinitol, D-chiro-inositol, bornesitol, myo-inositol, galactosyl-inositol, galactosyl-pinitol, ciceritol [43,55] Lupinus perennis D-pinitol, allo-inositol, D-chiro-inositol, bornesitol, myo-inositol [41] Medicago sativa D-pinitol, D-chiro-inositol, ononitol, scyllo-inositol, myo-inositol [41,47] Phaseolus polyanthus myo-inositol [44] Phaseolus vilgaris myo-inositol [44,46] Pisum sativum myo-inositol [44] Trigonella foenum-graecum D-pinitol, D-chiro-inositol, bornesitol, myo-inositol [41] Vicia faba myo-inositol [44] Vicia sativa myo-inostol [44] Vigna unaniculata ononitol, myo-inositol, galactosyl-inositol, galactosyl-ononitol [43][44][45] Hydrophyllaceae Phacella tanacetifolia A special mention as source of inositols deserves a plant-animal hybrid product, that is, bee honey, where quercitol (1,3,4/2,5-cyclohexanepentol), D-pinitol, 1-O-methylmuco-inositol and muco-inositol have been identified for the first time only in 2004 by Sanz et al [57]. In their work, 28 different honeys were analyzed finding that these compounds were present only in a limited number of samples, likely those collected by bees from wild plants.…”
Section: Fabaceaementioning
confidence: 99%
“…Their analyses revealed, for the first time in these species, the presence of chiro -inositol in addition to myo -inositol; furthermore, significant variations in chiro -inositol level as salinity increased suggested that this compound contributes to osmotic adjustment in the stressed plants, and that chiro -inositol response might be a physiological process for Limonium salt adaptation. Finally, in a very recent study, Foti et al [ 55 ] investigated the metabolic response of lentil ( Lens culinaris Medik, Fabaceae) when subjected to osmotic drought stress induced by PEG (polyethylene glycol). The authors found that not only a number of compounds, including myo -inositol, undergo differential accumulation, but also that the adaptive metabolic responses to osmotic drought stress operate under strong genetic control.…”
Section: Natural Occurrence Of Inositolsmentioning
confidence: 99%